TI_GERICHTE 52.2020.54 vom 20. Januar 2020 , Commesse pubbliche. Procedura selettiva. Modifica dell'offera - TI Tribunale d'appello (2020)
Commesse pubbliche. Procedura selettiva. Modifica dell'offera